2009
DOI: 10.1007/s12892-009-0103-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression levels of three bacterial blight resistance genes against K3a race of Korea by molecular and phenotype analysis in japonica rice (O. sativa L.)

Abstract: Bacterial blight, caused by Xanthomonas oryzae pv. oryzae (Xoo) is a destructive disease of rice in the major rice growing countries of Asia. In 2003, a serious bacterial blight epidemic occurred in the southwestern coastal areas in Korea, causing significant yield loss due to the emergence of a new race, K3a. IR24 near-isogenic lines containing Xa4, xa5, Xa7 and Xa21 genes conferred different degrees of resistance to the most virulent K3a isolate, HB01009 in an inoculation experiment in the greenhouse. Expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Mangeumbyeo is a japonica cultivar with good grain and cooking quality and high yield potential but it is highly susceptible to BB races. An IRBB57 NIL carrying Xa4 , xa5 and Xa21 genes in an IR24 genetic background conferred strong resistance to all Korean BB races, including K3a (Jeung et al 2006 ; Suh et al 2009a ). We have introduced the three BB resistance genes ( Xa4 + xa5 + Xa21 ) from IRBB57 into Mangeumbyeo through simultaneous foreground and phenotypic selection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mangeumbyeo is a japonica cultivar with good grain and cooking quality and high yield potential but it is highly susceptible to BB races. An IRBB57 NIL carrying Xa4 , xa5 and Xa21 genes in an IR24 genetic background conferred strong resistance to all Korean BB races, including K3a (Jeung et al 2006 ; Suh et al 2009a ). We have introduced the three BB resistance genes ( Xa4 + xa5 + Xa21 ) from IRBB57 into Mangeumbyeo through simultaneous foreground and phenotypic selection.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, increasing attention has focused on the accumulation of major disease resistance genes in crop plants. Pyramided lines carrying two, three or four bacterial blight resistance genes showed broad-spectrum and higher resistance than the lines with a single resistance gene (Gu et al 2005 ; Jeung et al 2006 ; Kim et al 2009 ; Singh et al 2001 ; Suh et al 2009a ). However, conventional breeding methods to improve rice cultivars for BB resistance have not found much success (Shin et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among other nearest genes, Xa3/Xa26 have been reported for resistance against three races, including K1, K2, and K3 but susceptible to K3a (Kim et al, 2015). Moreover, Suh et al (2009) reported that plants having Xa4 and Xa21 genes conferred strong resistance to K3a race. Another unknown locus on chromosome 11 for K3a race was located between an expressed protein and tropinone reductase2 gene, which helps in oxidoreductase activity in the cells.…”
Section: Discussionmentioning
confidence: 99%